Dynamic of Public Communication: Illocutionary Speech Acts Analysis in Ariana Grande’s Interview - Rahayu, Dwi; Nabila Zahratul Jannah; Rade Leony Siagian (Universitas Cokroaminoto Palopo, 2025)
This study aims to analyze the illocutionary acts that exist in Ariana Grande’s interview. This is a qualitative study with the data collected from the speech by both the interviewer and the interviewee on the YouTube channel entitled “Eternal Sunshine’, Wicked & Tour (Apple Music)”. The data from the interview was observed, transcribed and analyzed using Searle’s theory. The results of this study found a total of 60 data, which contains four types of illocutionary acts used, namely 19 assertive and directive respectively, 18 expressive, and 4 commissive. From the 60 illocutionary acts data, it shows that the most dominant speech act, assertive, shows the emphasis on her strong beliefs and commitment toward the film. The second most dominant speech act, directive, showcases her intention to promote the film and create engagement with the audience. Furthermore, Grande’s use of expressive speech acts show the intimate and emotional interaction and ambiance . In contrast, declarative types of illocutionary acts did not appear in this study indicating a lesser focus on commitments to future actions within the context of this interview. This study on Illocutionary Speech Acts enriches our understanding of public figures’ discourse, revealing their intentions, emotional states, and values.